Analysis of the Relationship Between Service Quality and Patient Satisfaction Levels - Rinda Purnama; Ratno Adrianto; Irfansyah Baharuddin Pakki (Indonesian Journal of Global Health Research, 2026)
Patient satisfaction is an important element in evaluating service quality by measuring the patient's response after obtaining health services by comparing it with what he expects. This study aims to determine the variables related to the quality of health services to outpatient satisfaction at the Tepian Baru Health Center, East Kutai Regency. This type of research uses a quantitative research method with a Cross Sectional Study approach. The sample size used in this study was calculated using the Lemeshow formula of 357 respondents. the data collection technique used a questionnaire developed from the dimensions of each variable in the study. The instrument was tested for validity and reliability before use. The validity test showed that all question items had a correlation coefficient greater than the r-table valu (0.361), indicating that the items were valid. Data analysis was carried out in three stages: univariate analysis to describe each variable, bivariate analysis using the Chi-Square test to determine the relationship between service quality dimensions and patient satisfaction, and multivariate analysis using multiple logistic regression to identify the most dominant variable. The results of the study showed that there was a positive and significant influence of the variables of Access/affordability, Efficiency, Human Relations, Comfort and Punctuality variables on the level of patient satisfaction at the Tepian Baru Health Center, East Kutai Regency. In this study, a multivariate test was also carried out with the multiple logistic regression method to see which variable had the most influence on the level of patient satisfaction, the results were obtained that the most dominant variable related to the level of patient satisfaction at the Tepian Baru Health Center was the Comfort variable with an Odd Ratio (OR) value of 52.367, meaning that the respondents gave their opinion on the importance of the role of comfort having a chance of 52 times related to the level of patient satisfaction at the Puskesmas New Edge.